P44 Improving advance care planning (ACP) documentation in frequent department of geriatric medicine (GRM) admitters with dementia in an asian hospital. Issue Volume 9: Issue (2019)Supplement 2 (3rd December 2019) - Ali, N; Piodena-Aportadera, M; Chong, R; Roslan, N; Fan, E; Ho, E
Abstract : Aim: To improve the percentage of completed ACP documentation of eligible recurrent admitters (3 or more admissions within the last 1 year with no prior ACP documentation on admission) with background dementia to ward 7D under department of GRM from 7% to 60% within 6 months Implementation: Micro and macro flow charts were created to evaluate the processes in conduct of ACP. Root causes for reduced ACP documentation were identified via Ishikawa diagram and Pareto Chart. Through multiple PDSA (Plan, Design, Study, Act) cycles, the following interventions were conducted: creation of mandated workflow for ACP, reminders to offer ACP and incorporation of ACP in clinical delivery through documentation of ACP status in interim discharge summary and daily clinical problem list. Results: Root causes for low ACP documentation were ACP was not mandatory as part of clinical service delivery, lack of educational materials on ACP and exclusion of ACP in clinical notes. After multiple interventions over 6 months, mean monthly completed ACP documentation rose from baseline of 5.5% to 28.8%, with highest achievable completion of ACP documentation at 50%. Though the target of completed ACP documentation was not met, there was an increase in the number of ACP discussions and documentation conducted by the department with increase awareness. This promotes a community of practice where ACP is offered readily. Conclusion: Changes in work processes and incorporation of ACP as part of clinical service delivery can improve ACP engagement in patients with dementia and their caregivers.